Effectiveness of contralaterally controlled functional electrical stimulation vs. neuromuscular electrical stimulation for recovery of lower extremity function in patients with subacute stroke: A randomized controlled trial - Huang, Songhua; Zhang, Yuqian; Liu, Peile; Chen, Yinglun; Gao, Beiyao; Chen, Chan; Bai, Yulong (Frontiers in Neurology, 2022)
Objective: To compare the efficacy of contralaterally controlled functional electrical stimulation (CCFES) versus neuromuscular electrical stimulation (NMES) for motor recovery of the lower-extremity in subacute stroke patients. Materials and Methods: Seventy patients within six months post-stroke were randomly assigned to CCFES group (n=35) and NMES group (n=35). Both groups underwent routine rehabilitation plus 20-minute electrical stimulation (CCFES or NMES) on ankle dorsiflexion muscles per day, 5 days a week, for 3 weeks. Ankle AROM (dorsiflexion), Fugl-Meyer assessment-lower extremity (FMA-LE), Barthel Index (BI), Functional Ambulation Category scale (FAC), 10 meters walking test and surface electromyography (sEMG) were assessed at baseline and end-of-intervention. Result: Ten patients did not complete the study (5 in CCFES and 5 in NMES), so there were totally 60 patients analyzed in the end. After 3-week intervention, FMA-LE, BI, Ankle AROM (dorsiflexion) and FAC increased in both groups (p<0.05). Patients in CCFES group showed significantly greater improvements only in the measurement of Fugl-Meyer assessment-lower extremity compared with the NMES group after treatment (p<0.05). The improvement in sEMG response of tibialis anterior by CCFES was greater than NMES (p<0.05). Conclusion: Contralateral controlled functional electrical stimulation can effectively improve the motor function of the lower limbs better than the conventional neuromuscular electrical stimulation in subacute patients after stroke, but the effect on improving the ability of walking such as walking speed was not good.